O3-S5.02 Frequent breakthrough genital HSV-2 shedding on standard and high dose valacyclovir. (10th July 2011) - Johnston, C; Saracino, M; Kuntz, S; Magaret, A; Schiffer, J T; Selke, S; Huang, Meei-li; Corey, L; Wald, A
Abstract : Background: Short, rapidly cleared, subclinical shedding episodes are the predominant form of HSV-2 reactivation in the genital tract. Valacyclovir 500 mg once daily (SD-VAL) reduces the risk of sexual transmission of herpes simplex virus type 2 (HSV-2) by only 48%. We hypothesised that short HSV-2 shedding episodes occur frequently on SD-VAL and that high dose (HD)-VAL could suppress such episodes of genital HSV-2 shedding. Methods: A randomised open-label crossover study using valacyclovir 500 mg daily (SD-VAL) vs valacyclovir 1 gm three times daily (HD-VAL) was conducted in HSV-2 seropositive, HIV seronegative persons with four or more genital herpes recurrences per year or laboratory confirmed primary genital HSV-2 infection in the previous 6 months. Each study arm lasted for 5 weeks, separated by 1 week wash out. Participants obtained genital swabs four times daily, which were assayed for HSV by quantitative PCR. The primary outcome was frequency of genital HSV shedding on each study arm; secondary outcomes included number and duration of HSV-2 shedding episodes and quantity of virus detected. Results: Forty-three participants collected 9981 genital swabs during the study period. 292 (5.8%) of 5008 swabs had HSV detected during SD-VAL, compared to 164 (3.3%) of 4973 on HD-VAL (IRR=0.52, 95% CI=0.43% to 0.63%, p<0.001). Episodes were shorter on HD-VAL (median 7 h, compared to 10 h on SD-VAL, p=0.03) and the median maximum copy number was lower on HD-VAL (3.0 log10 copy/ml vs 2.5 log10 copies/ml, p=0.001). However, the annual episode rate was the same regardless of dose; there were 55 shedding episodes over 3.89 person-years of follow-up during SD-VAL (14.1 episodes/year) and 65 episodes over 3.93 person-years during HD-VAL (16.5 episodes/year, p=0.34). Conclusion: Short bursts of genital HSV-2 reactivation persist during SD-VAL and HD-VAL. Compared to SD-VAL, HD-VAL decreased shedding frequency and episode duration but did not alter episode rate. These data may explain why risk of HSV transmission and HSV-specific genital inflammation persist even in the presence of antiviral therapy. More potent therapies are needed to completely suppress HSV-2 reactivation ClinicalTrials.gov number NCT00362297 .